ChemInform Abstract: Synthesis and in vitro Antitumor Screening of 2‐(β‐D‐xylofuranosyl)thiazole‐4‐carboxamide and Two Novel Tiazofurin Analogues with Substituted Tetrahydrofurodioxol Moiety as a Sugar Mimic. Issue 12 (14th March 2013) - Popsavin, Mirjana; Spaic, Sasa; Svircev, Milos; Kojic, Vesna; Bogdanovic, Gordana; Popsavin, Velimir
Abstract The known thiazofurin stereoisomer (VII) and two new thiazofurin analogues (XI) and (XII) are synthesized and evaluated for their in vitro antitumor activity.